War, Economic Strife, Climate Change: Understanding Intersectional Threats to Inclusion and Security - Roland Zarzycki; Leah Burch; Mustapha Sheikh (Social Inclusion)
When we discuss global security efforts, we must ask whom these initiatives genuinely serve. This volume seeks to address this question by presenting perspectives from scholars around the world on issues of inclusion and security, particularly for those who are marginalised by virtue of their indigenous background, ethnicity, age, gender, sexuality, disability, illness, socio‐economic position, and class. We ask why these vulnerable groups are often left to struggle alone. Are they being excluded from existing security frameworks—or are such frameworks even available? Furthermore, how do these global dangers affect their sense of safety, their trust in society, and their ability to access essential services? To capture this complex reality, we invited contributions not only from academics but also from NGOs, barristers, and practitioners with direct experience of these hardships. The resulting collection offers both conceptual analyses and case studies on specific issues affecting ethnic minorities, disabled individuals, and gender minorities.